2009
DOI: 10.1177/0192623308328544
|View full text |Cite
|
Sign up to set email alerts
|

Ferritin Expression in Rat Hepatocytes and Kupffer Cells after Lead Nitrate Treatment

Abstract: Lead nitrate induces hepatocyte proliferation and subsequent apoptosis in rat livers. Iron is a constituent of heme and is also required for cell proliferation. In this study, the expression of ferritin light-chain (FTL), the major iron storage protein, was investigated in rat livers after a single intravenous injection of lead nitrate. Western blotting and immunohistochemistry revealed that FTL was increased in hepatocytes around the central veins and strongly expressed in nonparenchymal cells. Some FTL-posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…The supernatant was used as an extract [36]. Spot density of ferritin band was normalized to the amount of protein, by loading equivalent amount of protein (5 µg), in each lane, for each liver extract analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…The supernatant was used as an extract [36]. Spot density of ferritin band was normalized to the amount of protein, by loading equivalent amount of protein (5 µg), in each lane, for each liver extract analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…The 19% greater level of activity of AST in the HePb group was a significant increase. In contrast, the concentrations of bilirubin, LDH 5 …”
Section: Resultsmentioning
confidence: 91%
“…This study was performed at 8 weeks of CF administration, because our previous study revealed that preneoplastic foci lacking BE expression developed in sensitive KS‐type rats at this time‐point. ( 12,22 ) α‐SMA, CD68 and CD34 were used as markers for the HSC, Kupffer cell and sinusoidal endothelial cell, respectively, ( 21 ) and the numbers of cells positive for the respective marker were compared between the KS‐ and NC‐type rat livers. Individual staining results are presented in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Apoptotic cell death was examined by the TdT‐mediated dUTP‐biotin nick end‐labeling (TUNEL) analysis, as reported previously. ( 21 )…”
mentioning
confidence: 99%